2011
DOI: 10.1130/b30314.1
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial response to paleo-equatorial climate fluctuations during the late Paleozoic ice age

Abstract: The Maritimes Basin of Atlantic Canada preserves a 12-km-thick stratigraphic succession deposited within a low-latitude, predominantly continental setting during the late Paleozoic. This paper examines the utility of using such successions for paleoclimate analysis, with specifi c reference to changes in fl uvial style. Modern rivers in the subhumid and semiarid tropics preserve a suite of features that are distinct from those in humid and arid environments. These features include an abundance of sedimentary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 82 publications
(109 reference statements)
2
65
0
1
Order By: Relevance
“…In an overview of the regional fluvial sedimentology, Allen et al (2011Allen et al ( , 2013 supported Rust et al's (1984) interpretation of the Springhill Mines Formation as recording a progressive shift from fixed-to meandering-channel bodies. They interpreted fluvial architecture and geometry as being compatible with prevailing interpretations of a (sub)humid seasonal climate during deposition of this unit (Calder 1994(Calder , 1998Falcon-Lang and Scott 2000;Utting et al 2010).…”
Section: Previous Sedimentological Studiesmentioning
confidence: 68%
See 1 more Smart Citation
“…In an overview of the regional fluvial sedimentology, Allen et al (2011Allen et al ( , 2013 supported Rust et al's (1984) interpretation of the Springhill Mines Formation as recording a progressive shift from fixed-to meandering-channel bodies. They interpreted fluvial architecture and geometry as being compatible with prevailing interpretations of a (sub)humid seasonal climate during deposition of this unit (Calder 1994(Calder , 1998Falcon-Lang and Scott 2000;Utting et al 2010).…”
Section: Previous Sedimentological Studiesmentioning
confidence: 68%
“…During relatively dry periods, flora and fauna may have been concentrated close to active channels in a situation similar to the waterhole model described by Falcon-Lang et al (2004). The presence of silicified cordaitalean logs in other Pennsylvanian units has been interpreted as recording increased aridity and/or a shift to better drained inland conditions Allen et al 2011;Ielpi et al 2014).…”
Section: Descriptionmentioning
confidence: 79%
“…A recent study has also reported such structures in the Boss Point and Little River formations (Allen et al 2011). Rygel and Gibling (2006) explored the numerous Joggins Formation channel bodies and their development in terms of intrinsic and extrinsic controls.…”
Section: Stratigraphy Sedimentology and Sedimentary Environmentsmentioning
confidence: 99%
“…Those intervals of global cooling and warming, fluctuating on time scales of 1 to 10 Myr, are thought to have been controlled by fluctuations in pCO 2 . Several recent studies have investigated the imprint of these dynamic changes of global climate on the low-paleolatitude record (e.g., Feldman et al, 2005;Bishop et al, 2010;Allen et al, 2011;Koch and Frank, 2011;Eros et al, 2012;Martin et al, 2012). In doing so, they noted the challenges entailed in deconvolving the effects of global climate change from those caused by the latitudinal drift of continental masses (Roscher and Schneider, 2006;.…”
Section: Introductionmentioning
confidence: 97%